Simultaneous measurement of liquid level and R.I. sensor using POF based on twisted structure - Muhammad Saleh Urf Kumail Haider; Chen Chen; Abdul Ghaffar; Sadam Hussain; Mujahid Mehdi; Laraib Unsa Noor; Sabir Ali Kalhoro; Min Liu (Scientific Reports)
Abstract In this paper, a dual-parameter liquid level and refractive index (R.I.) sensor is fabricated using three pieces of bare polymer optical fibers (POFs), which can independently and simultaneously sense the liquid level and R.I. The proposed sensor design utilizes the twisted coupling technique, in which two optical fibers are twisted and coupled with macro-bending. The liquid level measurement depends on the coupling loss, where the light is transmitted to emission fiber (EF) and twisted with coupled acceptor fiber (AF). The proposed liquid level sensor can measure depths up to 125 mm with a sensitivity of 8.03 nW/mm. Moreover, R.I. sensing depends on the twisted coupled macro-bending (TCMB) technique, where the EF generates bend loss and the AF couples the loss, where the coupled power varies due to the transformation in R.I. of coupling medium. The R.I. sensor revealing a notable sensitivity of -2663%/RIU and an impressive resolution of 3.754 × 10−4 in the different NaCl-saturated liquids featuring R.I. range extending from 1.333 to 1.361. The experimental findings indicate the sensor exhibits excellent stability and reliability. The sensor’s straightforward, comprehensive, and cost-effective design enables its application in chemical, petroleum, and other industries.